A novel label-free aptasensor based on target-induced structure switching of aptamer-functionalized mesoporous silica nanoparticles. Issue 122 (24th November 2015) - Du, Lili; Zhang, Yu; Du, Yan; Yang, Dongzhi; Gao, Fenglei; Tang, Daoquan
Abstract : A strategy for high-performance liquid chromatography detection of adenosine triphosphate was developed based on mesoporous silica nanoparticles functionalized with an aptamer as a cap. Abstract : In this study, a sensitive protocol for the high-performance liquid chromatography (HPLC) detection of adenosine triphosphate (ATP) based on mesoporous silica nanoparticles (MSN) functionalized with an aptamer as a cap has been designed. Aminopyrine (AP) is sealed in the inner pores of MSN with single-stranded DNA. In the presence of ATP, an ATP aptamer combines with ATP and escapes from a pore and thus opens the DNA biogate to release AP. The released signal tags can be easily read out by HPLC. The designed protocol provides sensitive HPLC detection of ATP down to 0.41 nM with a linear range of four orders of magnitude (from 1.0 nM to 10 μM) and has high selectivity toward its target ATP, which can be attributed to the large loading capacity and highly ordered pore structure of mesoporous silica nanoparticles, as well as the selective binding of the aptamer with ATP. This proof of concept might promote the application of ATP-responsive devices and also provide ideas for designing various target-responsive systems using other aptamers as caps.